Berkshire introduction - Morgan, Philip; Thorn, Frank; Thorn, Caroline (The University of Hull)
The introduction discusses the Hundreds, their rubrication, order, and revised name-forms; the state of the manuscript for the county; the editorial history of earlier versions of the notes, and the current state of the revision. Some material in this introduction derives from the original printed edition published by Phillimore (1979) and edited by Philip Morgan.